Surgical repositioning with omentalisation of an exposed subcutaneous ureteral bypass shunting port in a cat - Shi Min Lee; Jayson Tuan (Journal of Feline Medicine and Surgery Open Reports, 2024)
Case summary A 9-year-old, spayed, female domestic shorthair cat presented with an open wound approximately 1 cm in size with exposure of the left subcutaneous ureteral bypass (SUB) shunting port that was placed approximately 11 months before presentation. Primary closures were attempted twice before local wound management with omentalisation and repositioning of the port. The exposed port was lavaged topically with a polyhexanide and propylbetaine wound irrigation solution before omentalisation and repositioning, resulting in successful retention of the implant. Five months after revision and omentalisation, there was complete coverage and healing of the wound. Relevance and novel information Adequate topical treatment, repositioning and omentalisation could be a successful treatment option for the uncommon complication of SUB shunting port extrusion secondary to resistant local infection originating from the urinary tract.